2002
DOI: 10.1104/pp.004010
|View full text |Cite
|
Sign up to set email alerts
|

RASPBERRY3Gene Encodes a Novel Protein Important for Embryo Development

Abstract: We identified a new gene that is interrupted by T-DNA in an Arabidopsis embryo mutant called raspberry3. raspberry3 has "raspberry-like" cellular protuberances with an enlarged suspensor characteristic of other raspberry embryo mutants, and is arrested morphologically at the globular stage of embryo development. The predicted RASPBERRY3 protein has domains found in proteins present in prokaryotes and algae chloroplasts. Computer prediction analysis suggests that the RASPBERRY3 protein may be localized in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 60 publications
2
31
0
Order By: Relevance
“…Identical results were obtained in abnormal suspensor (sus) mutants (Schwartz et al 1994), and raspberry (rsy) mutants (Apuya et al 2002) of Arabidopsis thaliana.…”
Section: Plant Cell Tiss Organ Cultmentioning
confidence: 72%
“…Identical results were obtained in abnormal suspensor (sus) mutants (Schwartz et al 1994), and raspberry (rsy) mutants (Apuya et al 2002) of Arabidopsis thaliana.…”
Section: Plant Cell Tiss Organ Cultmentioning
confidence: 72%
“…Although it has been reported previously that chloroplasts are present in the late stages of Arabidopsis embryogenesis (Apuya et al, 2002;Apuya et al, 2001;GutierrezNava et al, 2004) and that chlorophyll fluorescence is widely used as a background marker in embryo imaging, to our knowledge a detailed description of the embryonic stages and cell types that contain chloroplasts have not been reported previously. In order to determine if stage specific patterns of chloroplast-containing cells are present during Arabidopsis embryogenesis, we have quantified chlorophyll fluorescence as a marker for plastids that have differentiated into chloroplasts.…”
Section: Introductionmentioning
confidence: 81%
“…Anterograde and retrograde signals between the nucleus and plastids have been demonstrated to participate in chloroplast biogenesis during early stages of embryogenesis (Woodson and Chory, 2008). Mutations in nuclear-encoded genes for chloroplast localized proteins are often embryonically lethal (Apuya et al, 2002;Hormann et al, 2004;Kubis et al, 2004;Lopez-Juez, 2007;Uwer et al, 1998;Xu and Moller, 2004;Yu et al, 2004). Additionally, TargetP predictions of 220 EMB genes, required for normal Arabidopsis embryo development, suggest that 32% of these genes are directed to chloroplasts (Tzafrir et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RSY3 encodes a novel protein that is localized in chloroplasts, and it has been suggested that RSY3 protein is required for chloroplast differentiation and embryonic development (Apuya et al 2002). However, the direct factors produced by the embryo proper to suppress the embryogenic potential of suspensor cells have not been identified in this mutant.…”
Section: Genetic Analysis Of the Interactions Between The Embryo Propmentioning
confidence: 99%